Case Report: An early-onset inflammatory colitis due to a variant in TNFAIP3 causing A20 haploinsufficiency - Zanatta, Laura; Biscaro, Francesca; Bresolin, Silvia; Marzaro, Maurizio; Sarcognato, Samantha; Cataldo, Ivana; Marzollo, Antonio; Martelossi, Stefano (Frontiers in Pediatrics, 2022)
Autoinflammatory diseases (AID) are a heterogeneous group of inherited conditions caused by abnormal activation of systems mediating innate immunity. Recent literature focuses on A20 Haploinsufficiency, an autoinflammatory disease with a phenotype resembling Behçet disease (BD). It is caused by loss-of-function mutations in TNFAIP3 gene that result in the activation of a pro-inflammatory pathway. In this case report we describe a one-year-old baby who came to our attention for hematochezia appeared at three months of age which was considered an expression of early-onset colitis. The following appearance of cutaneous inflammation Behçet-like and the positive family history concurred with the diagnosis of an autoinflammatory disease. Extended genetic tests in the patient allowed to identify a heterozygous variant in TNFAIP3 (NM_006290.4:c.460G>T, p.(Glu154Ter)), not previously described and not present in the GnomAD database. As a consequence the diagnosis A20 Haploinsufficiency was established and the appropriate management was started. The same TNFAIP3 variant was also found in her father who had suffered from recurrent oral aphthosis, vitiligo and thyroiditis since childhood. In conclusion, we described a young patient with a novel heterozygous mutation in TNFAIP3 who developed BD-like symptoms. We proposed that loss-of-function variants in TNFAIP3 may be associated with a very early-onset intestinal BD phenotype.